12-4x=2(6-2x)

Simple and best practice solution for 12-4x=2(6-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-4x=2(6-2x) equation:


Simplifying
12 + -4x = 2(6 + -2x)
12 + -4x = (6 * 2 + -2x * 2)
12 + -4x = (12 + -4x)

Add '-12' to each side of the equation.
12 + -12 + -4x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
0 + -4x = 12 + -12 + -4x
-4x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
-4x = 0 + -4x
-4x = -4x

Add '4x' to each side of the equation.
-4x + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4.8*3.7= | | -(8-m)=-(5m+8) | | 119=4x+3(5x+8) | | 5y-20=40 | | 2ab*4b^3= | | 4(4x+3)-2x=5 | | 25r^2+70r+45=-3 | | 16j-27=37 | | -3(x+2)-(x-2)=x+6 | | 10y+3x=456 | | 6a=9-5a | | 2k-3(2k-3)=44 | | 18x+15y=85 | | 5(j+4)+j=8 | | -152-4x=12x+56 | | 32+0.7x=50+0.3x | | 24x-16=160 | | 115+7x=3x | | 35z+25=40z | | 3x^2-24x+14=0 | | 4+(-3)x=11 | | -6-20=2x+12 | | 2(3x-1)=2x+22 | | 3000-36=7500 | | 5x+3(6x-9)=111 | | 62=56+48v-42 | | 2x+3+2-x=6 | | -172-11x=x+92 | | a+6=9+5a | | -5y-20=40 | | -3b-ac=c+4 | | 7.4x-9=7x+12 |

Equations solver categories